2010
DOI: 10.2196/jmir.1461
|View full text |Cite
|
Sign up to set email alerts
|

Providing Web-Based Feedback and Social Norms Information to Reduce Student Alcohol Intake: A Multisite Investigation

Abstract: BackgroundUnhealthy alcohol use among university students is cause for concern, yet the level of help seeking behavior for alcohol use is low within the student population. Electronic brief interventions delivered via the Internet present an alternative to traditional treatments and could enable the delivery of interventions on a population basis. Further evidence is needed of the effectiveness of Internet-delivered interventions and of their generalizability across educational institutions.ObjectiveOur object… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
96
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(104 citation statements)
references
References 34 publications
5
96
1
2
Order By: Relevance
“…Furthermore, research is also needed to examine the use of different formats of this novel parent normative feedback intervention. For example, research among college students has demonstrated the potential efficacy of web-based personalized normative feedback (Bewick et al, 2010; Neighbors et al, 2010; Walters, Vader, & Harris, 2007), in-person group interventions (LaBrie et al, 2010; LaBrie et al, 2008) and gender-specific normative feedback (Lewis & Neighbors, 2007; Neighbors et al, 2010). There is potential to adapt these approaches for use among college parents to further strengthen the effects of a norms-based PBI.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, research is also needed to examine the use of different formats of this novel parent normative feedback intervention. For example, research among college students has demonstrated the potential efficacy of web-based personalized normative feedback (Bewick et al, 2010; Neighbors et al, 2010; Walters, Vader, & Harris, 2007), in-person group interventions (LaBrie et al, 2010; LaBrie et al, 2008) and gender-specific normative feedback (Lewis & Neighbors, 2007; Neighbors et al, 2010). There is potential to adapt these approaches for use among college parents to further strengthen the effects of a norms-based PBI.…”
Section: Discussionmentioning
confidence: 99%
“…Here we found no influence on drinking intentions following exposure to messages designed to influence normative drinking perceptions. It may be that different social norms approaches are better suited, e.g., personalized feedback about how drinking behavior relates to specific norm reference groups (Moreira et al, 2009a,b;Bewick, 2010), rather than the use of messages about campus wide drinking norms, as was the focus of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…In this study perceived drinking norms were associated with individual differences in drinking behavior (i.e., heavier drinkers tended to overestimate how much their peers drank). A UK trial tested the effects of personalized social norm feedback on self-reported drinking via an internet intervention (Bewick, 2010), but as the social norms component was paired with other information it is not possible to draw conclusions about the effectiveness of the social norms information in isolation. In a large randomized control trial across 22 UK universities, Moreira et al (2009b) found that a personalized norm feedback intervention was not effective in reducing heavy drinking.…”
Section: Introductionmentioning
confidence: 99%
“…Investigaciones en otros contextos indican que el uso de incentivos mínimos (e.g. bolígrafos) 15 o pre-incentivos fomentaría una participación más cercana a la obtenida mediante cuestionarios en papel y lápiz y en entrevistas cara a cara 19 , las cuales fueron muy satisfactorias. Por otro lado, también han sido usados con éxito recordatorios complementarios como cartas o mensajes de texto 9,14 .…”
Section: Discussionunclassified
“…Este punto de corte es el recomendado para la detección de trastornos actuales por uso de alcohol de acuerdo con la 10 a revisión de la Clasificación Internacional de Enfermedades (CIE-10) 17 . Se escogió esta escala por ser una de las más utilizadas para evaluar problemas por uso de alcohol con cuestionarios online 19,20,21,22,23,24 . El consumo excesivo episó-dico de alcohol fue estimado con dos preguntas mediante el enfoque de cantidad-frecuencia graduada, i.e.…”
Section: Medidasunclassified